(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Describe the current status of full and timely vaccination for children under 1 year old in 4 communes of Yen Chau district, Son La province, in 2023. Subjects and methods: Using a cross-sectional study, combining qualitative and quantitative research. Quantitative and qualitative. Conducted research on 252 immunization records of children aged 12-24 months living in 04 communes Chieng On, Muong Lum, Chieng Hac, Tu Nang and 252 mothers/primary caregivers for the children. Results: The percentage of children who were fully vaccinated with 8 vaccines was 51.6%, of which full and on-time vaccination was 9%, and 33.7% were fully vaccinated and unscheduled. Fully vaccinated, on schedule with vaccines in lowland areas is higher than in highland areas and this rate is different among communes: Chieng Hac (61.9%), (50.8%), Tu Nang commune (Chieng Hac (61.9%), (50.8%). 49.2%) Chieng On (44.4%), p<0.05. The order of the vaccines is fully vaccinated on time: Hepatitis B vaccine 87.7%, BCG vaccine 80.2%, OPV 44.4%. The reasons why children are not vaccinated on schedule are: sick 68.6%, out of vaccine 52.6%, missed vaccination schedule 51.5% and 28.4% of children/mothers infected with Covid-19. Conclusion: It is necessary to provide adequate and timely vaccines; review the list of children who have not been fully vaccinated and organize vaccination for children; Strengthen the deployment of monthly mobile vaccination points; strengthen propaganda to raise people’s awareness about the complete immunization of children.